Identification of a subset of immunosuppressive P2RX1-negative neutrophils in pancreatic cancer liver metastasis - Xu Wang (Nature Portfolio, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive metastatic disease characterized by an immunosuppressive microenvironment. Here the authors show that a subset of P2RX1-negative neutrophils with immunosuppressive properties accumulate in PDAC metastatic liver tissues and promote tumor growth.